Modelling and analysis of induction preheating of moving filler wire for directed energy deposition - Cao, Ruofeng; Sun, Yongle; Suder, Wojciech; Chen, Xin; Li, Zhiyong; Williams, Stewart (Elsevier, 2026)
Induction preheating of filler wire is an emerging auxiliary process that allows precise control of wire temperature before melting by a main energy source in directed energy deposition (DED). This can enhance deposition rate and reduce defects. The induction heating mechanism for DED applications needs to be understood for establishing a robust process window that integrates coil design and key process parameters. This study investigates the evolution of electromagnetic and thermal fields during induction heating of a stainless-steel filler wire moving through a helical coil. A coupled electromagnetic-thermal model of a moving wire was developed to determine the magnetic flux, eddy current, temperature, and energy transfer efficiency. The wire temperatures predicted by the multiphysics model are consistent with experimental measurements under diverse conditions, with an error of less than 7 % after the heating reaches a steady state. The typical energy transfer efficiency for a wire diameter of 1.6 mm ranges in 3 %-9 %, which can be significantly enhanced through increasing the wire diameter and reducing the radial distance to the coil. The model enables a deeper understanding of the electromagnetic-thermal mechanisms governing both the transient and steady-state temperature distributions in the wire. In the steady state, the peak temperature is located immediately outside the exit end of the coil, and the temperature gradient across the wire diameter is marginal. A sensitivity analysis to identify dominant parameters was also carried out, showing that the wire feed speed (up to 150 mm/s), coil current (up to 700 A) and frequency (up to 500 kHz) are most influential. This study demonstrates an effective modelling approach to induction heating of moving wire, and it also provides critical insights for designing and optimising the induction coil and process for preheating filler wires in additive manufacturing and other similar processes (e.g. welding and cladding).
Keywords: 4014 Manufacturing Engineering; 40 Engineering; 4008 Electrical Engineering; 7 Affordable and Clean Energy; Mechanical Engineering & Transports; 49 Mathematical sciences; 51 Physical sciences; Induction heating; Wire feeding; Multiphysics model; Electromagnetic field; Preheating temperature; Wire arc additive manufacturing